The domain - Zdarsky, Chip (Image Comics, 2025)
A classic superhero story for those coming in fresh, and a fun meta story for readers of PUBLIC DOMAIN! When three best friends discover a crashed UFO, they also discover technology that gives them incredible abilities! But there's a catch: only one of them can use the powers at a time! Can their friendship survive the power's temptation? In the pages of Image's Eisner-winning series, PUBLIC DOMAIN, Syd Dallas and the team at Dallas Comics reimagine their classic character THE DOMAIN for a new audience, and...this is that comic! Collects THE DOMAIN #1-5